Diagrammatic mental representation: a methodological bridge. Issue 5 (20th October 2022) - Saint-Louis, Hervé; McEwen, Rhonda
Abstract : While computer-mediated user studies tend to rely on surveys, observations, focus groups, and ethnography, participant-generated mental model diagrammatic representation can yield valuable data involving complex and abstract user practices and behaviour. Computer-mediated research has struggled with eliciting users' beliefs of concrete representations in technology interactions. Using an investigation of authentication and user perceptions of security, we tested a method to elicit user mental model representations. We asked this overarching question: What are user perceptions of security when logging in to third-party apps and services via existing Facebook, Google, and Twitter accounts? Drawing from approaches to researching technology from the sub-fields of human-computer interaction, user studies, visual and risk communication, while incorporating methodological techniques from psychology on mental models, we offer a methodological innovation. We found evidence suggesting that a diagrammatic approach to representing mental models is feasible in addressing some of the challenges faced by existing computer-mediated approaches.